International Parities and Business Cycle Synchronization in the Asia Pacific Region - Chan, Tze Haw (2009)
The 1997 financial turmoil, in conjunction with the escalating global uncertainties and exchange rate volatilities, has revealed the need of APEs (especially East Asian) to formulate new development path towards sustainable growth. Yet, no ideal solution has been proposed and major concerns are now centered at finding an equilibrium position within macroeconomic trilemma: the incompatibility between capital mobility, monetary policy independence and a fixed (stable) exchange rate regime. The present thesis tries to tackle the issue from two standpoints. First, the extent of economic integration: (i) goods (and services) versus financial market integration; (ii) regional (within ASEAN+3+2+1) versus global (US, Japan, China) integration, and (iii) over time, for the pre- and post-liberalization period as well as the pre- and post-crisis period. Second, the choice of optimal exchange rate regime underneath the tendency towards regional integration. Two major analyses are being conducted. The first engaged with the international parities that include the PPP, UIP and RIP conditions (1976M1-2007M1). The latter then deals with the feasibility of OCA, which focus on the Business Cycle Synchronization assessment (1960-2004) among the selected APEs vis-à-vis the US, Japan and China. To accomplish the analyses on international parities, both univariate and panel-based unit toot tests are adopted. Endogenous breaks and the half-life estimation are conducted to capture the shocks adjustments towards the equilibrium, overtime. As for the OCA analyses, the band-pass filtering is used to construct business cycles. The ARDL modeling and UECM are further utilized to assess the long-and short-run co-movement of aggregate economic behavior as justification of common cycles and shocks synchronization. Several important findings are worth noting. First, the support for PPP is time-specific and time-dependent. Supports for PPP and goods markets integration were found when the data was extended to include the post-crisis period. PPP failure prior to 1997 is confirmed by the exchange rate misalignment of APEs. The evident that regional currencies were overvalued prior to the 1997 speculative attacks was more apparent for Taiwan, South Korea, Singapore, Thailand and the Philippines. However, regional authorities have shown some form of PPP-oriented rule as a basis for their exchange rate policy in the aftermath of Asian crisis, in order to maintain international competitiveness and to stabilize domestic income. In addition, supports for UIP are neither concrete, most probably due to the existence of time-varying risk premium as well as possible effects of central bank interventions especially among the developing East Asian. Hence, the commencement of monetary expansion to defend currency remains as policy debate. Then, RIP holds for all of APEs regardless of numeraire used, except South Korea-China. The finding coincides with the increased regional financial integration prompted by financial liberalization, technological breakthroughs, and growth in the capitalization among APEs. However, the variety of endogenous breaks occurred throughout the 1980s and 1990s suggests that financial markets are more vulnerable than the foreign exchange and goods markets. Empirically, APEs financial markets are still dominated by the US market though there is an increased of Japanese and Chinese influence in the post-liberalization era. Lastly, the co-movements of ASEAN-US-Japan-China cycles are confirmed but more evident when the post-crisis period is included. Nevertheless, both the long- and short-run modeling indicates that the idiosyncratic and common shocks of ASEAN economies are more identical to the Japanese experience rather than the US whereas the Chinese influences are on the rise. Hence, the formation of OCA will be more beneficial and less risky if Japan is included. In brief, the findings imply an improved integration process among the APEs. Empirical evidences, when putting together, have shown partial fulfilment of the three (out of five) fundamental criterions for OCA. Yet, macroeconomic disparities are still persisting especially among the emerging-developed markets. And, there is no evidence to support recent proposal of decoupling from the global markets. In other words, sub-group financial deepening, currency arrangements and early warning system construction are more feasible and open regionalism should be promoted. Moreover, the sequencing problem of trade and financial liberalization should be corrected in the process of building sustainable development.